The nationality policy of the Hungarian state and the Hungarian Polish community - Kaczmarek, Urszula (Balcanica Posnaniensia. Acta et studia, 2001)
The article is devoted to the nationality policy of contemporary Hungary and its significance for the functioning of the Polish national minority in that country. The author analyzes the changes that took place after 1989, when the democratization of the countries of Central and Eastern Europe led to a new approach to the protection of the rights of national and ethnic minorities. The aim of the study is to present the legal solutions adopted by the Hungarian state and to assess their impact on the development of the Polish community in Hungary. The research is based on a historical-legal method involving the analysis of legal acts, international documents, and studies concerning the history of the Polish diaspora in Hungary. The author points out that contemporary minority policy has moved away from an exclusive focus on individual rights and places greater emphasis on the collective rights of national communities. Particular importance is attributed to the Act on the Rights of National and Ethnic Minorities of 1993, regarded as one of the most innovative legal solutions in Central Europe. The article also presents the history of the Polish presence in Hungary, from eighteenth-century colonial settlement, through the political and economic emigration of the nineteenth century, to wartime refugees and post-war emigrants. In the conclusions, the author emphasizes that the solutions adopted by the Hungarian state created favorable conditions for the preservation and development of minority identity. Owing to appropriate legal guarantees, the Polish community was able to develop its own institutions, cultural and social activities, and maintain ties with its national heritage.